Patrons of the poor caste politics and policymaking in India - Lakshman, Narayan (New Delhi ; Oxford : Oxford University Press, 2011)
This text is a comparative study of the political economy of pro-poor policies in two Indian states: Karnataka and Tamil Nadu. By shedding light on the politics of resource allocation it attempts to show how traditionally rooted state policies benefit only certain sections of the population.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Poverty -- Government policy -- India -- Tamil Nadu; Poverty -- Government policy -- India -- Karnataka; Caste -- India -- Tamil Nadu; Caste -- India -- Karnataka